Chiquihuite Cave and America's Hidden Limestone Industries: A Reply to Chatters et al. (2nd January 2022) - Ardelean, Ciprian F.; Pedersen, Mikkel W.; Schwenninger, Jean-Luc; Arroyo-Cabrales, Joaquín; Gandy, Devlin A.; Sikora, Martin; Macías-Quintero, Juan I.; Huerta-Arellano, Vladimir; De La Rosa-Díaz, Jesús J.; Ocampo-Díaz, Yam Zul E.; Rubio-Cisneros, Igor I.; Barba-Pingarón, Luis; et al.
ABSTRACT: This paper is a reply to Chatters et al. (2021. "Evaluating Claims of Early Human Occupation at Chiquihuite Cave, Mexico." PaleoAmerica 8, doi:10.1080/20555563.2021.1940441), in which they raise a large number of doubts about the legitimacy of our claims of earlier-than-expected human presence at Chiquihuite Cave, in northern Zacatecas, Mexico, mainly questioning the artificial nature of the lithic assemblage and the integrity of our geological contexts. We respond to their main topics of concern, contributing arguments in defense of the human origin of the artifacts. We also include 10 examples of stone tools, with full descriptions and photographs, focusing on modified flakes that bear indicators of use-wear and intentional modification.